MOSS AS INDICATORS OF ANTHROPOGENICALLY DISTURBED FOREST AREAS - Baik Оксана (Actual Problems of Medicine and Pharmacy, 2023)
On the basis of the conducted research, it was established that under the influence of stress factors, such as hydrothermal regime and high light intensity, the synthesis of low-molecular antioxidants (soluble phenols, flavonoids, carotenoids, and anthocyanins) increases, which contributes to the stress resistance of moss plants. The research results indicate that the most significant increase in the content of low molecular weight metabolites in the dominant species of forest mosses occurred under the conditions of the highest level of disturbance of the forest ecosystem (clearing area), high temperatures, light intensity and low humidity. In addition, it was found that the increase in the content of low-molecular antioxidants correlates with the level of anthropogenic load on forest ecosystems. Therefore, the high content of soluble phenols, flavonoids, carotenoids and anthocyanins can serve as an indicator of anthropogenically disturbed forest areas.